The Concept of Data Model Pattern Based on Fully Communication Oriented Information Modeling (FCO-IM) - Fazat Nur Azizah; Benhard Sitohang; Guido P. Bakema; Oerip S. Santoso (ITB Journal of Information and Communication Technology, 2010)
Just as in many areas of software engineering, patterns have been used in data modeling to create high quality data models. We provide a concept of data model pattern based on Fully Communication Oriented Information Modeling (FCO-IM), a fact oriented data modeling method. A data model pattern is defined as the relation between context, problem, and solution. This definition is adopted from the concept of pattern by Christopher Alexander. We define the concept of Information Grammar for Pattern (IGP) in the solution part of a pattern, which works as a template to create a data model. The IGP also shows how a pattern can relate to other patterns. The data model pattern concept is then used to describe 15 data model patterns, organized into 4 categories. A case study on geographical location is provided to show the use of the concept in a real case.